2020
DOI: 10.1186/s12864-020-6550-z
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq reveals differential expression profiles and functional annotation of genes involved in retinal degeneration in Pde6c mutant Danio rerio

Abstract: Background: Retinal degenerative diseases affect millions of people and represent the leading cause of vision loss around the world. Retinal degeneration has been attributed to a wide variety of causes, such as disruption of genes involved in phototransduction, biosynthesis, folding of the rhodopsin molecule, and the structural support of the retina. The molecular pathogenesis of the biological events in retinal degeneration is unclear; however, the molecular basis of the retinal pathological defect can be pot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Pathway enrichment was performed from both KEGG and REACTOME databases. The top 10 pathways mutually identified in both databases and ranked by their p -value (Saddala et al, 2020 ) are shown in Figure 3 . Electron transport chains, citric acid cycle, nicotinamide scavenging, Alzheimer's disease and Huntington’s disease pathways were upregulated and identified from both the databases.…”
Section: Resultsmentioning
confidence: 99%
“…Pathway enrichment was performed from both KEGG and REACTOME databases. The top 10 pathways mutually identified in both databases and ranked by their p -value (Saddala et al, 2020 ) are shown in Figure 3 . Electron transport chains, citric acid cycle, nicotinamide scavenging, Alzheimer's disease and Huntington’s disease pathways were upregulated and identified from both the databases.…”
Section: Resultsmentioning
confidence: 99%
“…Zebrafish possess a remarkable ability to regenerate lost neurons in response to acute injury ( Nagashima and Hitchcock, 2021 ) and it remains unclear why mutants with progressive, chronic degeneration, such as cep290 and bbs2 , fail to initiate a regenerative response. Transcriptional changes in response to acute damage to the zebrafish retina have been extensively documented ( Kassen et al, 2007 ; Ramachandran et al, 2012 ; Sifuentes et al, 2016 ; Mitchell et al, 2019 ; Hoang et al, 2020 ; Kramer et al, 2021 ), while only a limited number of studies have examined transcriptional changes in retinal degeneration mutants ( Morris et al, 2011 ; Saddala et al, 2020 ). The goals of this study were to identify transcriptional changes that were common between two models of retinal ciliopathies and to ascertain if those differences could provide insight on the reasons why these mutants do not exhibit signs of regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The gene ontology for proteomics and microarray was performed using FunRich and PANTHER. , Gene IDs of the identified list of genes and proteins were recovered and were applied using the online databases to identify the pathways and for comparison analysis. Protein–protein interactions were studied in the STRING online database at the highest confidence level of 0.9.…”
Section: Methodsmentioning
confidence: 99%